The ability of AlBukhari to preserve the harmony between the Principles of the Science of History and the Science of Hadith in his book AlTarikh AlKabir “the Grand History” - Al – Leheabi, Saleh Muhammad Zeki Mahmood (Al-Adab Journal, 2020)
This research deals with a very important subject: the ability of AlBukhari to preserve the harmony between the science of history and the science of Hadith in his book AlTarikh AlKabir “The Grand History”. In addition to explaining the nature of criteria of Hadith collection adopted by AlBukhari in the mentioned book. For example, AlBukhari used to incorporate in each biography one chain of narration to refer through it or through the Matn (text) to the narrator. He may mention one chain of narration which is the most common. Sometimes he may use a group of chains of narration. He may increase them to reach ten which is very few in his book. Using such Hadith approach by AlBukhari has certain objectives: some are related to the biography of the narrator, others related to the persons mentioned in the chain of narration, and others related to the text, using relevant terminology etc. AlBukhari didn’t only report the chain of narration without knowledge. He was a critique in most cases and gives his opinion. Sometimes he says, “the chain of narration isn’t acceptable” or “not strong”, or “there is something wrong with the chain of narration”. AlBukhari may have doubt about the authenticity and correctness of the narration, or may have a doubt about the Shaikh’s meeting the student. Sometimes, he says “I do not know of he heard from Abi Al Zinad or not “. This means that Al Bukhari as a Hadith scholar used his incredible skills to add a lot to the science of history, through the process of criticism, assessment, analysis of content of texts and the scrutiny of chains of narration. Such basics transfer History from its general narrative context to an established science. The aim of this research is to clarify the scientific approach of AlBukari, with regards to texts he used in his book, AlTarikh AlKabir “The Grand History”. Sometimes he used to use the text in full, sometimes in parts, and then he repeats it with same chain of narration or with another chain, or uses many chains of narrations, and may only refer to the text, saying:(Thus, meaning, so forth, so on…). Also, we aim to show the scientific approach of AlBukhari in mentioning the names of Shaikhs from whom the Hadith narrated, saying “It was heard from, from, it was heard, heard from”. Also, mentioning the names of narrators, saying “It was heard from him, it was narrated from him, from him”. In addition to that AlBukhari used a group of words on amendment and documentation when mentioning the biography of narrators, such as saying “Trustworthy, his Hadith is well known, sincere”.